Radiopharmaceutical application of TRK-950, an anti-CAPRIN-1 therapeutic antibody - Yuki Majima; David Kryza; Mitsuaki Sanada; Jacqueline Sidi-Boumedine; Patrick Mehlen; Benjamin Gibert; Jean-Yves Blay; Fumiyoshi Okano (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Tumor imaging or therapy using cancer specific carriers combined with a radioisotope has huge potential. In radiopharmaceutical development, it is important to ensure target specificity and minimal binding to normal tissues for both tumor detection and treatment. In previous studies, we identified CAPRIN-1 as a cancer-specific antigen, which is widely expressed on the cell surface membrane in many types of solid cancers, and created TRK-950, a humanized monoclonal antibody raised against CAPRIN-1, followed by conducting clinical development. In this proof-of-concept study, we prepared radiolabeled form of TRK-950 and investigated their potential as tumor imaging or therapeutic agents. Methods An [111In]In-DOTA-TRK-950 was prepared and administered to tumor-bearing mice, and its tumor accumulation and pharmacokinetics were evaluated with SPECT/CT imaging. Next, the anti-tumor effect of a [177Lu]Lu-DOTA-TRK-950 was evaluated. Additionally, radiolabeled TRK-950-F(ab’)2, an antibody fragment of TRK-950, was similarly evaluated for their potential. Results At 72 h after administration of [111In]In-DOTA-TRK-950, tumor accumulation was high at 24.8% IA/g for 4T1 and 18.9% IA/g for HT-29, both of which are CAPRIN-1-high cancer cells, while tumor accumulation remained low at 7.5% IA/g for MNNG/HOS, which are CAPRIN-1-low cancer cells. Regarding therapeutic evaluations, strong anti-tumor effects and prolonged survival were observed after administration of [177Lu]Lu-DOTA-TRK-950 to 4T1 and HT-29 tumor-bearing mice. Furthermore, these results were also observed in the 4T1 tumor-bearing model with radiolabeled TRK-950-F(ab’)2, which has shorter pharmacokinetics. Conclusion This study demonstrates that radiopharmaceuticals targeting CAPRIN-1, including radiolabeled TRK-950 and TRK-950-F(ab’)2, have high potential as radiopharmaceuticals.